Investigating the abundance and flight period of bark beetles (Coleoptera: Curculionidae: Scolytinae) over elevational gradients in Sitka spruce forests. (2nd October 2020) - Williams, David T.; Cull, Tom; Forster, Jack
Abstract: A warming climate, as predicted under current climate change projections, is likely to influence the population dynamics of many forest insect species. Numerous bark beetle species in both Europe and North America have already responded to a warming climate by significantly expanding their geographical ranges. The aim of the current study was to investigate how populations of bark beetles within stands of Sitka spruce, a widely planted non‐native commercial plantation tree species in the U.K., were likely to respond to a warming climate. Experimental plots were established in stands of Sitka spruce over elevational gradients in two commercial forest plantations, and the abundance and emergence times of key bark beetle species were assessed over a 3‐year period using flight interception traps. The air temperature difference between the lowest and highest experimental plot in each forest was consistently >1°C throughout the 3‐year period. In general, the abundance of the most dominant bark beetle species ( e.g. Trypodendron, Dryocoetes, Hylastes spp.) was higher, and emergence times tended to be earlier in the year at the lower elevation plots, where temperatures were higher, although not all bark beetle species responded in the same manner. The results of the study indicated that, under the projected future climate warming scenarios, monoculture Sitka spruce stands at low elevations may potentially be more vulnerable to significant outbreak events from existing or invasive bark beetle species. Hence, consideration of establishing more resilient forests of Sitka spruce by diversifying the species composition and structure of Sitka spruce stands is discussed.